2022
DOI: 10.1111/den.14221
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of linked color imaging for the detection of obscure early gastric cancer: Multivariate analysis of 508 lesions

Abstract: Objectives Early gastric cancers (EGCs) of the elevated type or with submucosal invasion are easily found by routine endoscopy. However, most early cancers are challenging to detect because of subtle morphological or color differences from surrounding atrophic mucosa and intestinal metaplasia. Linked color imaging (LCI) enhances mucosal color difference, making it easier to detect EGCs. The aim of this study is to clarify the advantages and possible disadvantages of LCI for screening for obscure EGC. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Further investigations focusing on EGC are desired to determine whether LCI is more effective in a general population for gastric cancer screening. More recently, Khurelbaatar et al [ 67 ] showed that when compared with conventional WLI, LCI significantly improved the visibility of EGC regardless of differences in lesion morphology, histology, location, depth of invasion, and Hp status, which may explain the improved detection rates and reduced miss rates previously reported.…”
Section: Lci For Screening Of Egcmentioning
confidence: 97%
See 3 more Smart Citations
“…Further investigations focusing on EGC are desired to determine whether LCI is more effective in a general population for gastric cancer screening. More recently, Khurelbaatar et al [ 67 ] showed that when compared with conventional WLI, LCI significantly improved the visibility of EGC regardless of differences in lesion morphology, histology, location, depth of invasion, and Hp status, which may explain the improved detection rates and reduced miss rates previously reported.…”
Section: Lci For Screening Of Egcmentioning
confidence: 97%
“…Non-experts placed the biopsy mark more accurately with LCI (82.3% vs. 87.2%, P < 0.001). Non-experts were indicated to prefer LCI over WLI Khurelbaatar et al [ 67 ] 2022 Retrospective/SC 508 EGCs from 456 patients Images of EGCs LCI significantly improved visibility of EGC regardless of differences in lesion morphology, histology, location, depth of invasion, and Hp status compared with conventional WLI Ishida et al [ 28 ] 2022 Retrospective/SC 99 EGC lesions from 88 patients Videos of EGCs and gastric mucosa captured using LED and laser endoscopy LED-WLI and LED-LCI can be used to visualize EGCs with non-inferiority to Laser-WLI and Laser-LCI Haruma et al [ 68 ] 2022 RCT/MC 1502 patients (patients with a history of gastrointestinal cancer) Real-time observation The detection rate of upper gastrointestinal neoplasms tended to be higher with LCI than with WLI among patients who underwent ultra-slim endoscopy Khurelbaatar et al [ 69 ] 2022 Retrospective/SC 52 EGCs and 29 nonmalignant lesions Video including cases of EGC or gastric atrophy alone using standard and ultra-thin endoscopies Ultra-thin LCI had a higher diagnostic sensitivity and significantly higher visibility scores and color difference than standard WLI SC single-center, MC multicenter, RCT randomized controlled trial, EGC early gastric cancer, IM intestinal metaplasia, LCI linked color imaging, WLI white-light imaging, BLI blue laser imaging, LED light-emitting diode, Hp Helicobacter pylori , M-Chromo-LCI magnifying linked color imaging with indigo carmine dye, M-BLI magnifying blue laser imaging, MR map-like redness, IC indigo carmine contrast method, CI confidence interval, AIM acetic acid indigo carmine mixture
Fig. 2 PRISMA 2009 flow diagram describing the selection of the studies included in our review
…”
Section: Lci For Screening Of Egcmentioning
confidence: 99%
See 2 more Smart Citations
“…As IEE screening for gastrointestinal malignant lesions has progressed, LCI has been demonstrated to be a brighter IEE technique than WLI and thus more useful in screening for lesions because it provides improved visualization of changes in redness, allowing easy recognition and detection of EGCs ( 18–20 ). Recently, two clinical randomized studies have reported the efficacy of LCI in detecting EGC.…”
Section: Discussionmentioning
confidence: 99%